2014
DOI: 10.1007/s10265-014-0666-7
|View full text |Cite
|
Sign up to set email alerts
|

Progressive migration and anagenesis in Drimys confertifolia of the Juan Fernández Archipelago, Chile

Abstract: A common mode of speciation in oceanic islands is by anagenesis, wherein an immigrant arrives and through time transforms by mutation, recombination, and drift into a morphologically and genetically distinct species, with the new species accumulating a high level of genetic diversity. We investigate speciation in Drimys confertifolia, endemic to the two major islands of the Juan Fernández Archipelago, Chile, to determine genetic consequences of anagenesis, to examine relationships among populations of D. confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…Among living species, anagenesis has occurred in cyprinid teleosts15 and it has produced genetic diversity among oceanic island plants1617. Anagenesis gained currency in studies of dinosaur evolution with Horner et al .’s1 landmark study that found evidence for phyletic evolution in four lineages of dinosaurs, including tyrannosaurs, from the Late Cretaceous of the American West.…”
mentioning
confidence: 99%
“…Among living species, anagenesis has occurred in cyprinid teleosts15 and it has produced genetic diversity among oceanic island plants1617. Anagenesis gained currency in studies of dinosaur evolution with Horner et al .’s1 landmark study that found evidence for phyletic evolution in four lineages of dinosaurs, including tyrannosaurs, from the Late Cretaceous of the American West.…”
mentioning
confidence: 99%
“…; López‐Sepúlveda et al . ). Those results are concordant with the hypothesis that anagenetic speciation in the islands has, over time, been associated with an increase in genetic diversity and has erased the footprint of a genetic bottleneck that may have resulted from the original colonization of the islands.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to prior investigations in other JF genera such as Drimys (López‐Sepúlveda et al . ) and Myrceugenia (López‐Sepúlveda et al . ), Rhaphithamnus is an example of anagenetic speciation in which there is generally lower genetic diversity in the insular species than in their continental relatives, presumably the result of the founder effect associated with the recent colonization of the island.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern has been found with Drimys confertifolia , endemic to both islands but having diverged around 9–10.8 Ma (Marquínez et al ., ). Recent studies using amplified fragment length polymorphisms and nuclear microsatellites (López‐Sepúlveda et al ., , ), however, have proposed that all of these species have a more recent origin. In these population‐genetic studies, no molecular clock was employed and it is not impossible that the direct ancestors of these lineages may have already become extinct.…”
Section: Discussionmentioning
confidence: 99%